Hubungan Antara Kualitas Diet dengan Status Gizi pada Siswa SMAN 9 Surabaya - Ussy Nastiti; Triska Susila Nindya (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
This study was conducted in response to the increasingly complex nutritional issues among adolescents, reflected in the coexistence of undernutrition and overnutrition within the same population, which are closely associated with dietary consumption patterns. The research aimed to investigate the relationship between diet quality and the nutritional status of students at SMAN 9 Surabaya. A quantitative approach with a cross-sectional design was employed, involving 85 participants selected based on the estimated sample requirement for correlation analysis. Dietary intake data were collected using two non-consecutive 24-hour food recalls and subsequently assessed using the Diet Quality Index for Adolescents (DQI-A). Nutritional status was determined through BMI-for-age calculations in accordance with the World Health Organization standards. Data analysis was performed using correlational testing and Chi-Square analysis to identify differences in proportions. The findings revealed that the respondents’ diet quality remained suboptimal, while most students were categorized as having normal nutritional status, although cases of undernutrition and overnutrition were still identified. A significant association was found between diet quality and nutritional status (p = 0.001), indicating that better diet quality tended to be linked with normal nutritional status. Based on the DQI-A components, dietary quality demonstrated a significant relationship with nutritional status (p = 0.007), whereas dietary diversity (p = 0.597) and dietary equilibrium (p = 0.507) showed no significant associations. These findings highlight that diet quality, particularly food selection patterns, plays an important role in determining adolescent nutritional status. Therefore, improving nutritional conditions requires more intensive nutrition education interventions focusing on healthy food choices, increased fruit and vegetable consumption, and controlled intake of sugar, salt, and fat, supported consistently by both individuals and the school environment.